Atuação do pedagogo na perspectiva da inclusão escolar: a articulação entre o professor do atendimento educacional especializado e o da sala de aula comum - Estevam, Mariana Karoline Dias Coelho (2019)
In order to discuss about the articulation of the pedagogue´s work with high school teachers and the specialized educational assistance, the dissertation was based on the school inclusion of students with intellectual disabilities in a state public school in the city of Barra de São Francisco/ ES. This is a qualitative research, having as methodology the case study. The research subjects were the effective teachers and those in temporary character designation of the regular classroom and the specialized educational attendance. As data production instruments, semi structured interviews were conducted, participant observation and focus group. The theoretical framework consists on Paulo´s Freire discussions about the concept of dialogicity. Through dialogue with teachers, it was possible to know the reality and context of the school and the challenges presented in the process of school inclusion of students with intellectual disabilities enrolled at high school. The research illustrates that a significant number of teachers are interested, participate and propose change practices that meets and effectively include these students. Some teachers recognize about are their role, but they point out difficulties on perform it, claiming that they still need the help with working with such a diverse group, beyond guidance and support regarding planning and elaboration of different assessment, in different languages and periods to meet everyone. In this sense, the final product was built, materialized in a formation training, which allowed participants to share their doubts and daily demands, concerning students with intellectual disabilities, and to elaborate, together with the group of teachers, strategies that would create opportunities to construct knowledge and ensures the education quality for these students.